2010
DOI: 10.1007/s11947-010-0428-z
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Water-Jet Technology as a Method of Improving the Quality of Post-Harvest Processing

Abstract: In tropical countries, the processing steps of peeling and cutting are carried out mainly by hand under ideal conditions for microbial growth. For the production of high-quality, safe products, procedures, which minimize the direct contact between product and personnel, must be applied. A pilot lot was developed that combines robotics, water jet, and image processing techniques in an integrated process of peeling and cutting tropical fruits for minimizing losses in the process and increase hygiene standards re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…The waterjet cutting technique utilizes high‐pressure waterjet energy to separate the target samples, which can deeply evade thermal injury and cross‐contamination. A high‐pressure waterjet automatic cutting apparatus integrated with a waterjet cutting system, image acquisition system, and process control system was developed for fruit cutting (Carreño‐Olejua et al., 2010). Compared to the cutting performance of a normal knife and handheld slicer, the waterjet cutting technique was beneficial for reduced processing loss and oxidation.…”
Section: Other Advanced Cutting Techniques For Food Processingmentioning
confidence: 99%
“…The waterjet cutting technique utilizes high‐pressure waterjet energy to separate the target samples, which can deeply evade thermal injury and cross‐contamination. A high‐pressure waterjet automatic cutting apparatus integrated with a waterjet cutting system, image acquisition system, and process control system was developed for fruit cutting (Carreño‐Olejua et al., 2010). Compared to the cutting performance of a normal knife and handheld slicer, the waterjet cutting technique was beneficial for reduced processing loss and oxidation.…”
Section: Other Advanced Cutting Techniques For Food Processingmentioning
confidence: 99%
“…Wulfkuehler et al () and Wulfkuehler, Dietz, Schmidt, Weiss, and Carle () also showed that water jet cutting could replace blade cutting in the study of cutting chicory by water jet and cutting chicory with new blade, which avoided the interruption of blade replacement in processing and cross contamination of microorganisms. To improve the water jet cutting technology Carreño‐Olejua, Hofacker, and Hensel () utilized pressure sensor and image acquisition technology for analysis of the area of interest of melon and apple, the water jet technology in fruit and vegetable slices has obtained the remarkable effect through the second order partial derivative of the image acquisition, especially for the symmetry is better. To study different types of fruits and vegetables, the machine design of fuzzy controller was adopted in the later stage to adjust the water pressure, cutting direction, distance between nozzle and fruits and vegetables, cutting speed.…”
Section: Food Segmentation and Identification Technologymentioning
confidence: 99%
“…Food industry demands more effective cutting process (Palma-Salgado et al 2014 ). The water jet cutting system controls pressure with a water barrier that prevents the movement of fl uids and fl ushes away the potentially damaging enzymes from the tissues (Carreño-Olejua et al 2010 ). The purifi ed water increases the quality of the fresh-cut products with the absence of blades and knives; and reduces the possibility of microbial contamination and minimizes the oxidation.…”
Section: Water Jet Cuttingmentioning
confidence: 99%